2007
DOI: 10.1111/j.1740-8261.2007.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Mri Characteristics and Histology of Bone Marrow Lesions in Dogs With Experimentally Induced Osteoarthritis

Abstract: Signal changes within the bone marrow adjacent to osteoarthritic joints are commonly seen on magnetic resonance (MR) images in humans and in dogs. The histological nature of these lesions is poorly known. In this study, we describe the MR imaging of bone marrow lesions adjacent to the stifle joints of dogs with experimental osteoarthritis over 13 months. Histology of the proximal tibia at the end of the study was compared with the last MR imaging findings. In five adult dogs, the left cranial cruciate ligament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 17 publications
8
72
0
1
Order By: Relevance
“…Using radiographs in a cross-sectional study, Beuf et al [15] also demonstrated that the loss of trabecular bone in the femurs of OA patients correlated with the severity of the disease as assessed by the radiography-based Kellgren-Lawrence scale. Interestingly, such hypersignal bone lesions were recently evaluated histologically and appear to correspond mainly to fibrosis, myxoedematous degeneration and/or cellular infiltrate of the bone marrow [16]. Altogether, these findings strengthen the hypothesis that the subchondral bone changes may play a role in the genesis of cartilage lesions.…”
Section: Osteoarthritissupporting
confidence: 55%
“…Using radiographs in a cross-sectional study, Beuf et al [15] also demonstrated that the loss of trabecular bone in the femurs of OA patients correlated with the severity of the disease as assessed by the radiography-based Kellgren-Lawrence scale. Interestingly, such hypersignal bone lesions were recently evaluated histologically and appear to correspond mainly to fibrosis, myxoedematous degeneration and/or cellular infiltrate of the bone marrow [16]. Altogether, these findings strengthen the hypothesis that the subchondral bone changes may play a role in the genesis of cartilage lesions.…”
Section: Osteoarthritissupporting
confidence: 55%
“…Several studies have reported signs of microfracture in areas containing BML. 8,9 This finding together with the presence of active bone formation and live osteocytes in the area, 10 however, points to increased repair capacity, which seems the key for the spontaneously reversible course of this syndrome. Increased marrow adiposity has also been reported in some case reports on BML.…”
Section: Imagingmentioning
confidence: 96%
“…It was not observed by Barrett et al (2009), despite the use of higher field strength devices. Martig et al (2007) described the development of changes during the 13 months after the induction of osteoarthritis using the Pond-Nuki model by low-field MRI. They observed changes in the bone marrow of different sizes, variously located and with different signal intensity.…”
Section: Bonesmentioning
confidence: 99%
“…It was a new way of imaging characterized by better contrast resolution of a soft tissue in comparison with traditional radiography (Baird et al It is assumed that low-field magnetic resonance has a field strength of between 0.2T and 0.4T (Konar and Lang 2011). Other authors reported less than 0.15 T (Baird et al 1998a) or 0.15T to 0.3T (Sabiston et al 1987, Martig et al 2007). Whereas high-field magnetic resonance has a magnetic strength of 1 to 1.5T (Nolte-Ernsting et al 1996, Libicher et al 2005 or higher.…”
Section: Introductionmentioning
confidence: 99%